2012
DOI: 10.20452/pamw.1256
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines in the saliva of patients with active and non-active Crohn's disease

Abstract: IntroductIon Crohn's disease (CD) is a chronic granulomatous inflammatory disease of the entire gastrointestinal tract. Its etiology is unknown. The disease manifests itself with exacerbation (and then remission) of such symptoms as abdominal pain, fever, and weight loss, and is associated with many general and gastrointestinal complications. 1 Therapy involves the use of mesalazine and azathioprine. In active CD, corticosteroids and anti-tumor necrosis factor α (TNF-α) are introduced. 2,3 Since the first desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 25 publications
7
36
0
Order By: Relevance
“…Similarly, elevated salivary IL-1β, IL-6, and TNF-α levels in CD patients and an elevated IL-8 level in the saliva of patients with bowel disease were also reported. 58,59 Unexpectedly, the elevated level of inflammatory biomarkers in UC patients was similar to or slightly higher than that observed in CD patients, regardless of differences in disease states between IBD patients (Supplementary Fig. S4 and Table S5).…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, elevated salivary IL-1β, IL-6, and TNF-α levels in CD patients and an elevated IL-8 level in the saliva of patients with bowel disease were also reported. 58,59 Unexpectedly, the elevated level of inflammatory biomarkers in UC patients was similar to or slightly higher than that observed in CD patients, regardless of differences in disease states between IBD patients (Supplementary Fig. S4 and Table S5).…”
Section: Discussionsupporting
confidence: 58%
“…TNF-a has been shown to lead to a reduced olfactory regeneration [47]. Increased levels of circulating TNF-a [48] are present in IBD patients' serum and saliva [49]; therefore, a comparable pathomechanism can be assumed for the effects seen in this study. Recent genetic data [50] suggest a substantial overlap of genetic susceptibility in IBD, as well as other autoimmune diseases such as psoriasis and ankylosing spondylitis.…”
Section: Discussionmentioning
confidence: 56%
“…Szczeklik et al . have found elevated levels of pro-inflammatory cytokines IL-6, IL-1β and TNF-α in the saliva of patients with active CD along with manifestation of the specific oral lesions [48]. Similarly, Nielsen et al .…”
Section: Oral Manifestations Of Ibdsmentioning
confidence: 96%
“…In patients with active CD, salivary IL-1β, IL-6, and TNF-α levels were higher than in patients with inactive disease and controls. Elevated salivary IL-6 and TNF-α levels correlate with specific oral lesions [29]. Results of our study have shown higher concentrations of TNF-α and IL-6 as well as levels of IL-6/TGF-β and IL-17/TGF-β ratios in patients with CD compared to patients with UC, indicating a predominance of pro-inflammatory Th-1 and Th-17 immune response in CD (summarized in Table 1) [10].…”
Section: Immunological Background Of Ibdmentioning
confidence: 99%